USE AND EXPLOIT THE INTERNET ON INTERNET SERVICE PROVIDERS - Firman Dinar; Susi Wagiati, Ir Susi Wagiati, Ir (Jurnal Sistem Informasi, 1996)
Areas of the Internet itself can not be separated from communication techniques,because the Internet is formed with the development of highly advancedcommunication techniques. Other areas that affect the development of the internet isdata communications. Thus although the usefulness of the Internet itself relates toother fields, such as business, education and others.Internet usage can be very much research, from the project, formerly a militaryresearch project. and are quite visible results in the civilian field is marketing, internetmarketing engineering where with the right to make our products become famous.